Economic well-being among single mothers: the effects of materialism, stress, savings behaviour and compulsive buying behaviour - Mat Rahim, Fatin Farwizah; Abd Rahim, Husniyah; Osman, Syuhaily; Othman, Mohd Amim (HR Management Academic Research Society, 2022)
Economic growth has often been measured by income and productivity. The rise of the highly commercialised modern world has opened up the possibilities to look beyond numbers and introduced the concept of well-being in measuring a country’s performance. Efforts should be made especially among the vulnerable groups of population to ensure equal growth of the economic well-being. Single mothers often deal with economic, financial and psychological issues that make them much vulnerable to the dynamic movement of the economics. Therefore, this study aims to examine the effects of materialism, stress, savings behaviour and compulsive buying behaviour with single mothers’ economic well-being. The sample was selected by using a multi-stage random sampling which conducted among single mothers in Peninsular Malaysia. Results divulged that stress and compulsive buying behaviour had a significant negative influence on economic well-being. Additionally, compulsive buying behaviour had mediated the influence of materialism and stress on economic well-being. These findings suggest that managing the factor of materialism, stress and compulsive buying behaviour is crucial in alleviating the economic well-being of the single mothers. Further implications and suggestions for future research are also discussed accordingly.